Breast self-examination web site of the institute of oncology Sremska Kamenica vs. breast self-examination web sites in English language and languages of former Yugoslavia - Zdravković Svetozar; Devaja-Striber Dubravka (Archive of Oncology, 2002)
Breast self-examination web site of the Institute of Oncology Sremska Kamenica was designed in 2000 year and since then it has had about 490 visits, i.e. one visit by day approximately. The site was presented at the 6th Annual World Congress on the Internet in Medicine "Mednet 2001" in Udine, Italy, from November 29 to December 2, 2001. The next phase in our project is to improve its contents to increase its popularity. To achieve this we compared our site with similar sites in English language and languages of former Yugoslavia. The results of this comparison are presented in this paper. To find the sites in all languages we used search engine Google.com and following key words: "breast self-examination" (English language), "samopregled dojke" (Serbian and Croatian languages) "Samopregledovanje dojk" (Slovenian language) and "Samopregledot na dojkata" (Macedonian language). Some additional aspects of breast self-examination such as its validity as a screening tool and its influence on breast cancer mortality were also involved. Our aim was to emphasize the importance of further development of telemedicine services in general, and particularly the importance of primary care and early detection, including breast self-examination as integral parts of teleoncology services.